Influence of a laser pulse on thermoelasticity with temperature dependence under the dual-phase-lag model using improved modified extended tanh function method - Rabie, Wafaa B.; Ahmed, Hamdy M.; Syied, Abdallah A.; Abd-Elmonem, Assmaa; Suoliman, Nagat A.A.; Ismail, Mohamed F. (Results in physics, 2024)
In this paper, the improved modified extended tanh function method (IMETFM) is introduced for analyzing the influence of laser pulse on a thermo-elastic with temperature-dependence under a dual phase lag model (DPL). Nonlinear thermo-elasticity examines cases in which a material’s response to changing thermal loads causes considerable changes in both its geometry and material properties. This field is crucial for effectively describing real-world phenomena, such as thermal stresses in large-scale structures, the behavior of materials at high temperatures, and the intricate interactions between mechanical and thermal fields. The proposed method generated a variety of exact solutions featuring distinct free parameters, including hyperbolic, rational, bright solitons, singular solitons, dark solitons, exponential, polynomial, and Jacobi elliptic solutions. Additionally, some of the results for displacement component, temperature, and stress tensor are presented through graphical illustrations. •Improved modified extended tanh function method .•Nonlinear thermo-elasticity.•Exact Solutions.•Impact of laser pulses.